CONTEMPORARY MYTHOLOGIES – TRADITION, SYNCHRONISM, PROXIMITY - Xenia Negrea (Annals of the University of Craiova for Journalism, Communication and Management)
Nicu Gavriluță, Why do we like superheroes? The mythology and symbolism of the Marvel movies, Polirom, Iași, 2022